Against the new economic imperialism: some reflections - Michie, J; Oughton, C; Wilkinson, F (2002)
Classical political economy recognised that what needed analysing, explaining, and acting on was an economic system inextricably linked to the wider political and social systems. Smith and Ricardo, as well as Marx, saw class and the distribution of income as key. Neoclassical economics replaced these social and collective categories with the individual consumer and the marginal product of labour as the fundamental analytical categories—the "political" having been discarded. Yet even one of the founders of neoclassical economics, Alfred Marshall, would barely recognise nor accept what is today presented as economic analysis, ignoring as it does the key industrial and organisational detail underlying production. The "new political economy" claims to incorporate insights from other disciplines. But far from enriching economic analysis, these new strands of theory simply impose the assumptions and methods of neoclassical economics. We argue that this new economic imperialism needs to be replaced with a genuinely multidisciplinary and interdisciplinary approach to analysing economic issues.